EFEKTIVITAS SISTEM INFORMASI DAN MOTIVASI TERHADAP DISIPLIN KERJA DAN PERANANNYA DALAM MENINGKATKAN KEPUASAN KERJA DAN KINERJA PEGAWAI SATUAN KERJA PEMERINTAH DAERAH KABUPATEN BOYOLALI - BRM. Suryo Triono; Adi Penawan; Aris Tri Haryanto (STIE AUB Surakarta, 2020)
ABSTRACT This study aims to find out, analyze and prove empirically the Effectiveness of Information Systems and Motivation Against Work Discipline and Its Role in Increasing Job Satisfaction and Employee Performance of SKPD, Boyolali Regency. The analysis technique used is to use the instrument test which includes validity and reliability testing, linearity test, regression analysis, path analysis, t test, F test, test coefficient of determination and correlation analysis. The results showed that: Information and motivation systems have insignificant influence on work discipline. Information systems, motivation and work discipline have a significant effect on job satisfaction. Information systems, motivation and work discipline have no significant effect on employee performance. Job satisfaction has a significant effect on employee performance. The results of the F test can be concluded together information system variables, motivation, work discipline and job satisfaction affect employee performance in SKPD, Boyolali Regency. The total R2 value of 0.956 can be interpreted as variations in Employee Performance at the SKPD in Boyolali Regency, explained by Information System variables, Motivation, Work Discipline and job satisfaction of 95.6% and the remaining 4.4% explained other variables outside the research model as examples of competence, training and so on. The influence of the information system on job satisfaction is the most dominant influence because it has the highest value compared to other influences. Keywords : Information System, Motivation, Work Discipline, Job Satisfaction, Employee Performance